KNOWLEDGE AND TREATMENT SKILLS IN THE FIELD OF PSYCHOSOCIAL COUNSELLING - Nevenka Podgornik (Innovative Issues and Approaches in Social Sciences, 2015)
The article presents the basic knowledge and treatment skills in the field of psychosocial counselling. It includes knowledge, skills, personal characteristics, and the ethics of a professional worker, the method of psychosocial approach with and individual and a group, as well as a collective social work. The basic definition of the knowledge and treatment skills in the article is presented by the concept of a working relationship in a social world and by the concepts of modern social work – power perspective, participation ethics, treatment skills, and treatment of the present time. The article also presents the key definitions of social work in the counselling and power processes. The establishing of social-working relationship includes the use of the language, the directing of the dialogue and other methods of postmodern social work.